2023
DOI: 10.3390/medicina59020370
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Morphology and Fragment Mapping of Complex Proximal Humeral Fractures

Abstract: Background and Objectives: Proximal humerus fractures (PHFs) are common in the elderly, but the treatment results are often poor. A clear understanding of fracture morphology and distribution of cortical bone loss is important for improved surgical decision making, operative considerations, and new implant designs. The aim of this study was to develop a 3D segmentation fracture mapping technique to create a statistical description of the spatial pattern and cortical bone loss of complex PHFs. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…This may be related to the fact that the higher density of the articular surfaces was less susceptible to fracture, and the fractures in the patients included in the study by Hasan et al may have been the result of stronger trauma ( Tingart et al, 2003 ). In addition, Mys et al (2023) found that the incidence of fracture in the anatomical neck was lower, while in our study, the incidence of fractures was higher in the lower, posterior, and upper parts of the anatomical neck. Thus, the fracture morphology of complex PHFs was slightly different from that of all types of PHFs (including simple fractures).…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…This may be related to the fact that the higher density of the articular surfaces was less susceptible to fracture, and the fractures in the patients included in the study by Hasan et al may have been the result of stronger trauma ( Tingart et al, 2003 ). In addition, Mys et al (2023) found that the incidence of fracture in the anatomical neck was lower, while in our study, the incidence of fractures was higher in the lower, posterior, and upper parts of the anatomical neck. Thus, the fracture morphology of complex PHFs was slightly different from that of all types of PHFs (including simple fractures).…”
Section: Discussioncontrasting
confidence: 54%
“… Mys et al (2023) recently published a study on fracture morphology, which explained the complex morphology of PHFs by mapping 50 cases of complex PHFs. Most of the findings were in line with our results, with a high frequency around the surgical neck and articular fractures were infrequent ( Mys et al, 2023 ). However, despite many similarities with the research of Hasan et al in fracture morphology, the incidence of fracture in the intramuscular groove and articular surfaces was significantly different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations